In Vitro and In Vivo Antibacterial Activities of Heteroaryl Isothiazolones against Resistant Gram-Positive Pathogens - Pucci, Michael J. (American Society for Microbiology, 2007)
The activities of several tricyclic heteroaryl isothiazolones (HITZs) against an assortment of gram-positive and gram-negative clinical isolates were assessed. These compounds target bacterial DNA replication and were found to possess broad-spectrum activities especially against gram-positive strains, including antibiotic-resistant staphylococci and streptococci. These included methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-nonsusceptible staphylococci, and quinolone-resistant strains. The HITZs were more active than the comparator antimicrobials in most cases. For gram-negative bacteria, the tested compounds were less active against members of the family Enterobacteriaceae but showed exceptional potencies against Haemophilus influenzae, Moraxella catarrhalis, and Neisseria spp. Good activity against several anaerobes, as well as Legionella pneumophila and Mycoplasma pneumoniae, was also observed. Excellent bactericidal activity against staphylococci was observed in time-kill assays, with an approximately 3-log drop in the numbers of CFU/ml occurring after 4 h of exposure to compound. Postantibiotic effects (PAEs) of 2.0 and 1.7 h for methicillin-susceptible S. aureus and MRSA strains, respectively, were observed, and these were similar to those seen with moxifloxacin at 10× MIC. In vivo efficacy was demonstrated in murine infections by using sepsis and thigh infection models. The 50% protective doses were ≤1 mg/kg of body weight against S. aureus in the sepsis model, while decreases in the numbers of CFU per thigh equal to or greater than those detected in animals treated with a standard dose of vancomycin were seen in the animals with thigh infections. Pharmacokinetic analyses of treated mice indicated exposures similar to those to ciprofloxacin at equivalent dose levels. These promising initial data suggest further study on the use of the HITZs as antibacterial agents.